RELATIONSHIP MARKETING IN THE DIGITAL ENVIRONMENT: CHALLENGES AND OPPORTUNITIES - ROZHKO, Victor; BRAZHNIK, Daniil (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the evolution and current state of relationship marketing in a digital environment where the internet and social networks have become the primary communication channels. Through an analysis of the latest global statistics on spreading of the internet connection, social media usage, and average of time which spends on the internet daily. The study highlights the critical importance for businesses to establish a robust and regular online presence. The research emphasizes the necessity of transforming traditional marketing concepts to align with the realities of the 21st-century digital landscape. At the core of the investigation is the introduction and analysis of the "digital moment of truth." This concept is defined as a key, often decisive, point of interaction where a customer encounters and forms an impression of a company not through direct human contact, but through its abstracted, unified online form. This interaction can occur across various digital touchpoints, including official corporate pages, search engine results, influencer reviews, video platforms, and news articles. The study methodically explores two critical dimensions. Firstly, it identifies the key development prospects for relationship marketing in this context. These prospects are intrinsically linked to strategic branding—including the use of mascots and effective narratives and the construction of a multi-channel, responsive feedback system that prioritizes customer engagement. Secondly, the article provides a detailed examination of the primary threats and challenges inherent in building marketing relationships within the digital sphere. These include the gradual loss of anthropocentric principles as interactions mostly become mediated through interfaces; the significant risks of customer manipulation through sophisticated psychological techniques and misinformation; and the excessive commercialization of relationships, where simulated friendship are leveraged purely for immediate profit, potentially eroding genuine trust. To counter these challenges and harness the identified prospects, the article proposes a balanced, holistic solution. Long-term relationship building in the digital age requires the thoughtful integration of efficient digital communication tools with opportunities for authentic, live human interaction. Furthermore, it is imperative for companies to ensure a high degree of operational and ethical transparency, openly sharing information about their leadership, practices, and values. Ultimately, a sustainable strategy must remain firmly focused on understanding and fulfilling the genuine, non-manipulated needs of the customer, recognizing that long-term loyalty is built on a foundation of trust and mutual value, which can not be created by their own.